Senior Entrepreneurship (SE) As a Way of Active Ageing: A Case of Poland - Beata BIEŃKOWSKA (Communications of International Proceedings, 2022)
Senior Entrepreneurship (SE) can be considered as an opportunity for professional activation of eldelry people. Senior entrepreneurship is a relatively new topic. Its development requires a profound recognition of the group that has an income mainly from pension benefits. SE is a relatively new topic and not fully recognized when it comes to the conditions and methods of supporting the professional activity of elderly people in Poland. Support for SE requires defining the concept and focusing on a group that has a certain level of income from pension benefits, but still wants to actively participate in social life. It seems that this rapidly growing group of citizens is not sufficiently supported in terms of entrepreneurship. This paper is an attempt to verify the hypothesis that the development of SE, as a factor that positively affects the quality of elderly people’s lives and mitigates the negative aspects of population ageing, requires an in-depth analysis and application of specific forms of support. The analysis of this issue was divided into such specific problems as definition of the concept of SE (literature review); characteristics of Polish seniors’ potential; and gathering the opinions of respondents- senior entrepreneurs on the business acitivit at older age. The study utilized an analysis of secondary data, sample survey carried out in two groups of respondents and the structured intervies with three senior entrepreneurs. .
Keywords: entrepreneurship; seniors; demography; labor market